2014
DOI: 10.1056/nejmoa1308130
|View full text |Cite|
|
Sign up to set email alerts
|

A Dominant-NegativeGFI1BMutation in the Gray Platelet Syndrome

Abstract: The gray platelet syndrome is a hereditary, usually autosomal recessive bleeding disorder caused by a deficiency of alpha granules in platelets. We detected a nonsense mutation in the gene encoding the transcription factor GFI1B (growth factor independent 1B) that causes autosomal dominant gray platelet syndrome. Both gray platelets and megakaryocytes had abnormal marker expression. In addition, the megakaryocytes had dysplastic features, and they were abnormally distributed in the bone marrow. The GFI1B mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
169
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 150 publications
(180 citation statements)
references
References 23 publications
(34 reference statements)
9
169
1
1
Order By: Relevance
“…However, despite the interest of this study, X-linked inheritance is not a characteristic for GPS neither is the presence of red cell abnormalities (Table I). Strikingly, like for GFI1B, GATA1 deficiency leads primarily to defects of collagen-induced platelet aggregation this is also not the case for classic GPS [8,28,34].…”
Section: Gata1 Gene Defects and Plateletsmentioning
confidence: 85%
See 2 more Smart Citations
“…However, despite the interest of this study, X-linked inheritance is not a characteristic for GPS neither is the presence of red cell abnormalities (Table I). Strikingly, like for GFI1B, GATA1 deficiency leads primarily to defects of collagen-induced platelet aggregation this is also not the case for classic GPS [8,28,34].…”
Section: Gata1 Gene Defects and Plateletsmentioning
confidence: 85%
“…Both wildtype and truncated GFI1B transcripts were present in platelets and CD341 cells from an affected family member while expression studies in the Mag01 leukemia cell line showed the mutant protein to cause reversal of transcriptional repression of the TGFBR3 gene, encoding transforming growth factor beta receptor III, a known target for GFI1B [27]. This study was quickly followed by the report of another truncating mutation in GFI1B in a European family with MTP and a moderate to severe bleeding diathesis [28]. As blood smears showed "gray" platelets for affected family members these authors considered GFI1B as a gene causal of an autosomal dominant form of GPS.…”
Section: Gfi1b Transcription Repressormentioning
confidence: 90%
See 1 more Smart Citation
“…Similarity with the autosomal inherited disorder gray platelet syndrome (GPS) has been observed concerning deficiency of platelet a-granules and splenomegaly [4,6,9]. But in contrast to GPS due to NBEAL2 or lately discovered GFI1B mutations, where myelofibrosis has been found characteristic [9,10], there have been no previous reports of bone marrow (BM) fibrosis in XLTT or other GATA1 exon 4 mutation disorders [6,11].…”
Section: Introductionmentioning
confidence: 91%
“…The ectopic expression of the hematopoietic stem cell marker CD34 on megakaryocytes, together with their dysplastic appearance, are features that have been described for dominant GFI1B mutations. 7 The observed pale, grayish platelet staining pattern might reflect a GPSlike phenotype. However, this term should be used cautiously, as the "grey platelet syndrome" is associated with NBEAL2 mutations.…”
Section: A B E C Dmentioning
confidence: 98%